Improving the quality of local honey in Bongkasa Pertiwi Village, Badung Regency - I Gede Pasek Mangku; I Gusti Bagus Udayana; I Made Suwitra (Universitas Muhammadiyah Magelang, 2022)
This community service program was carried out in the “Sarining Trigona Pertiwi” group, Bongkasa Pertiwi Village, Abiansemal District, Badung Regency. This community service goal is to improve honey bee farming by increasing group expertise in developing nectar-producing plants. The methods used in this service activity include counselling, practice, and evaluation. The result of the program carried out was that there was an improvement in honey post-harvest techniques according to the materials and SOPs provided. The honey produced meets SNI standards, but the process of reducing the water content of honey is constrained by equipment. Management and group members have understood the legal regulations that need to be complied with in developing a honey business as an effort to prevent future internal problems.